PENDIDIKAN TENTANG SISTEM EKONOMI KERAKYATAN DALAM HUKUM ADAT MINAHASA DENGAN METODE VALUE CLARIFICATION TECHNIQUE SEBAGAI METODE PENCAPAIAN EFEKTIFNYA - Lombok, Lesza Leonardo (Forum Ilmu Sosial, 2014)
Minahasa is one of the tribes in Indonesia, located in the province of North Sulawesi with an agricultural background are very diverse with indigenous culture, especially in the customs of the farm. By having a large area and is rich in natural resources, the Minahasa tribe is famous for its variety of crops are abundant and quality. Although the nation's economic crisis hit Indonesia, Minahasans remained as one of the tribes rich, even becomingone of the backbone of the nation in overcoming the economic crisis have tribesm economic, value clarification technique resulted in the outcome - his produce. This is supported by the local communities in the Minahasa area of democratic economic system in building their economy by leveraging existing resources, called Mapalus. Value - the value that exists in this Mapalus systems qualify to be the one teaching to the world of education today. Methods Value Clarification Technique (VCT) is one of the appropriate methods to assist in the implementation of the system Mapalus teaching to students. Therefore, this study aimed to describe what a democratic economic system used in the customary law of Minahasa, reviewing VCT as an educational method, and examine the implementation of VCT in Mapalus system itself. By using normative research methods - empirical, the authors find that the system is a system Mapalus continuous cooperation of the people, and by using the VCT application in the education system can be done by combining a wide range of expertise, work together in the find and fix a problem, and provision of public confidence in the lower classes in the management of natural resources.